YOGA AND CROSS-CULTURAL COMMUNICATION IN MULTICULTURAL ENVIRONMENTS - Ni Luh Sinar Ayu Ratnadewi; I Nyoman Sueca (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2024)
The journal focused on investigating the transformative role of yoga within diverse cultural contexts. In an era characterized by unprecedented multiculturalism and global interaction, yoga emerges as a powerful cultural bridge, enhancing cross-cultural understanding and fostering inclusion. This journal invites rigorous academic exploration of yoga's multifaceted influence. It welcomes research spanning historical roots, cultural adaptations, and psychological dynamics of yoga practice within multicultural societies. Interdisciplinary dialogue is encouraged, with a focus on psychology, communication, anthropology, sociology, and cultural studies, providing a comprehensive view of yoga's cross-cultural impact. Ethical considerations related to the practice and propagation of yoga are explored, alongside practical applications in promoting unity, well-being, and psychological resilience within diverse communities. The journal also engages with future directions in yoga research and application. Committed to academic rigor, "Yoga as a Cultural Bridge" aims to be a scholarly repository for in-depth inquiry into yoga's pivotal role in bridging cultural divides and fostering inclusive, harmonious societies. It promotes appreciation for cultural diversity and the shared human experience while advancing understanding of yoga as a cultural bridge.